Optimization of the Transmission Ratio by Fuel Consumption - Kosenko, E. E.; Marchenko, J. V.; Marchenko, E. V.; Popov, S. I.; Izyumov, A. I. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2024)
Introduction. The issues of ensuring optimal fuel consumption modes are the subject of constant research in the field of vehicle operation. Works in the field of reducing fuel consumption in most cases are devoted to the study of the design of power units, transmission or aerodynamic features of the body of cars. At the same time, the issues of determining the optimal laws of control of unsteady movement from the point of view of the synthesis of algorithms for controlling the movement of a car have not been considered. To optimize the transmission ratio of cars with unsteady movement, the authors of the work carried out analytical calculations to simplify the synthesis of motion control algorithms, which in turn allowed reducing fuel consumption. The aim of the work was to determine the optimal transmission ratio, which allowed solving the problem of synthesizing vehicle control to reduce fuel consumption. Materials and Methods. The synthesis of algorithms for controlling the movement of a car considered in the work was based on the application of the needle variation of L.S. Pontryagin to invariant features of the real movement. An analytical method was used to estimate energy efficiency of vehicle performance, which was based on determination of optimal transmission ratio of motor vehicles taking into account minimum fuel consumption. The presented method took into account the amount of torque transmitted from the engine crankshaft to the transmission elements, which, depending on the engine power, was realized in the form of traction force on the wheels of the car. Results. The law of optimal change in the transmission gear ratio during acceleration of the car in a minimum time was built. The problem of determining the optimal transmission ratio of the vehicle in the case of driving the vehicle at a constant speed and constant fuel supply and in the case of accelerating the vehicle to a given speed at a constant fuel supply, when the condition ε = const was met, was solved. The result of the considered case of applying the optimal law of change in the transmission gear ratio was the minimization of fuel consumption under restrictions on acceleration (traction force) and speed of the car. Discussion and Conclusion. The use by the authors of the analytical method for determining the transmission ratio of a car, as well as the use of this method in practical calculations for a car with given characteristics, showed the possibility of solving the problem of synthesizing vehicle control using a mathematical apparatus. This was confirmed by the built graphical dependence based on the results of the calculations. The considered cases of movement made it possible to determine the analytical dependencies of the optimal transmission ratio and the speed of the car. The initial data obtained by analytical relationships are applicable for cars with a mixed control mode.